2019
DOI: 10.3389/fpsyt.2019.00639
|View full text |Cite
|
Sign up to set email alerts
|

Postdecision Evidence Integration and Depressive Symptoms

Abstract: Background: Metacognition, or the ability to reflect on one’s own thoughts, may be important in the development of depressive symptoms. Recent work has reported that depressive symptoms were associated with lower metacognitive bias (overall confidence) during perceptual decision making and a trend toward a positive association with metacognitive sensitivity (the ability to discriminate correct and incorrect decisions). Here, we extended this work, investigating whether confidence judgments are more malleable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 52 publications
6
30
0
Order By: Relevance
“…The confidence bias also correlated with depression severity (Hancock et al, 1996) and improved in recovered patients (Fu et al, 2005). Conversely to confidence bias, depressive symptoms do not seem to affect metacognitive efficiency (Moses-Payne et al, 2019; Rouault, Seow, et al, 2018).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The confidence bias also correlated with depression severity (Hancock et al, 1996) and improved in recovered patients (Fu et al, 2005). Conversely to confidence bias, depressive symptoms do not seem to affect metacognitive efficiency (Moses-Payne et al, 2019; Rouault, Seow, et al, 2018).…”
Section: Introductionmentioning
confidence: 78%
“…Conversely to confidence bias, depressive symptoms do not seem to impact metacognitive efficiency (Moses-Payne, Rollwage, Fleming, & Roiser, 2019;Rouault, Seow, Gillan, & Fleming, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we additionally found that early adolescents (12-13 years), and male participants, showed heightened confidence, in spite of the same level of performance across all age groups and in both sexes. Although this did not relate to advice taking behaviour, overall confidence has been found to be associated with self-esteem and psychiatric symptoms dimensions such as anxious-depression, compulsivity and intrusive thoughts (Moses-Payne, Rollwage, Fleming, & Roiser, 2019;Rouault, Seow, Gillan, & Fleming, 2018). Further, integration of evidence post-decision, a similar process to advice-taking, has been shown to be associated with depressive symptoms (Moses-Payne et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Experimental evidence suggests that these facets of metacognitive ability are dissociable from task performance, and may have a distinct neural and computational basis [25][26][27][28][29][30][31]. Interestingly, self-reported mental health symptoms have been linked to changes in metacognition, often in the absence of differences in task performance [32][33][34][35]. Developing a biologically-motivated model of metacognition has the potential to cast light on how this dissociable mechanism is implemented at a circuit level, as well as provide a direct bridge between circuitlevel dysfunction and psychopathology.…”
Section: Introductionmentioning
confidence: 99%